CHARACTERISTICS OF THE ISLAMIC EDUCATION MODEL OF NUSANTARA - Duwi Miyanto (TAWASUT, 2025)
In this discussion only focus on the Character of The Model of Islamic Education Nusantara, in it discusses the model of education. This refers to science by ordering reading as the basis of science. The command to "read" in the verse is called twice the request to the Prophet (s), and then the command to all his people. Reading is a means to learn and the key to science, both etymologically in the form of reading the letters written in books, and terminology that is reading in a broad sense, meaning reading the universe (ayatul-kaunThis type of study approach uses a hermeneutic approach that is an approach that seeks to interpret symbols in the form of text or concrete objects to find meaning and meaning. Hermeneutics is one of the approaches that uses linguistic logic. That is to make an explanation and understanding by using the "meaning of the word"and then the meaning of language as the basic material. This approach is called linguistics which is a method to interpret facts, data and symptoms. In this context, the study in question is an attempt to interpret the texts of the literature relevant to the theme of the study, by expressing or quoting the statements of a text, then interpreting them according to the mindset built. Data collection method through library research is a pure research/ research. In data analysis using content analysis method, the collected data is then analyzed by content analysis method. To explore what the Islamic Education Model of Nusantara is related to its characteristics. The findings in this study are the idea of The Islamic Education Model of Nusantara to evoke the spirit of Islam.developing educational objectives, teacher aspects, aspects of learners, materials delivered, educational tools used and environmental aspects, moderate attitudes (al-wasathiyah) in education.